Wedge two-layer medium ultrasonic plane wave compounding imaging based on sign multiply coherence factor combined with delay multiply and sum beamforming. (April 2022) - Luo, Lin; Tan, Yuanhao; Li, Jinlong; Zhang, Yu; Gao, Xiaorong
Abstract: Ultrasonic phased array coherent plane wave compounding has a fast imaging speed, but the imaging quality is severely affected by noise, especially the imaging quality in the case of wedge two-layer medium, which is a problem worthy of study. In this paper, a wedge two-layer medium ultrasonic coherent plane wave compounding imaging based on the sign coherence weighting delay multiply and sum (DMAS) beamforming is proposed. The sign multiply coherence factor (SMCF) is proposed according to the correlation of the received data. The experimental results show that the SMCF weighted DMAS (DMAS-SMCF) method can significantly improve the contrast ratio and resolution of wedge two-layer medium plane wave imaging, and show its application capability in related applications.